It's all analytics! : the foundations of AI, big data, and data science landscape for professionals in healthcare, business, and government - Burk, Scott William, 1961-; Miner, Gary (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"Professionals are challenged each day by a changing landscape of technology and terminology. In recent history, especially the last 25 years there has been an explosion of terms and methods born that automate and improve decision-making and operations. One term called Analytics is an overarching description of a compilation of methodologies. But, AI (Artificial Intelligence), statistics, decision science, optimization which have been around for decades has resurged. Also, things like business intelligence, On-line Analytical Processing (OLAP) and many, many more have been born or reborn. How is someone to make sense of all this methodology, terminology? This book, the first in a series of three, provides a look at the foundations of artificial intelligence and analytics and why readers need an unbiased understanding of the subject. The authors include the basics such as algorithms, mental concepts, models, and paradigms in addition to the benefits of machine learning. The book also includes a chapter on data and the various forms of data. The authors wrap up this book with a look at next frontiers such as applications and designing your environment for success, which segue into the topics of the next two books in the series"--
"A Productivity Press Book."
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence; Decision making; Visual analytics; Big data